Decentralization as a Post‐Conflict Strategy: Local Government Discretion and Accountability in Sierra Leone1. (24th January 2015) - Edwards, Benjamin; Yilmaz, Serdar; Boex, Jamie
Summary Sierra Leone has made progress in recovering from a decade‐long civil war, in part due to decentralization. As a post‐conflict stabilization strategy, decentralization has been effective in satisfying the desire for more equitable political representation, and three rounds of peaceful elections have strengthened democratic norms. However, more needs to be performed to strengthen local governments in order to address regional horizontal inequity. Solely political decentralization is not sufficient in addressing regional differences in pro‐poor service delivery, which was a key driver of conflict. It requires broader commitment to establish a functioning local government system, including central government subscription to the tenets of administrative and fiscal decentralization. Though Sierra Leone has remained stable in terms of political violence, recent data show that the nation has not made great strides in addressing weak and inequitable social service delivery. This paper argues that this stagnation is a product of the incomplete nature of the post‐conflict stabilization strategy of decentralization and that correcting this failure will require strong commitment from the central government to implementing the full measure of the existing legal framework for decentralization. Copyright © 2015 John Wiley & Sons, Ltd.